Panic-gogy in the COVID-19 pandemic: developing online teaching self-efficacy by management faculty. (27th September 2022) - Sharma, Daneshwar; Pankaj, Prabhat
The COVID-19 pandemic forced educational institutes worldwide to shift to online education in an emergency situation. The faculty used panic-gogy as a pedagogy tool to shift their courses to synchronous or asynchronous online mode. Focus group discussions were conducted to gather the panic-gogy experiences of management faculty. Bandura's self-efficacy building information sources were used as a framework to analyse management faculty's experiences. Vicarious experiences and social persuasions emerged as the most influential information sources of self-efficacy building. The analysis led to implications for management education administrators and human resources personnel related to training management faculty in online teaching and facilitating the process of building online teaching self-efficacy in management faculty.